Incorporating an Alternating Donor–Acceptor Structure into a Ladder Polymer Backbone. Issue 27 (18th April 2016) - Kass, Kim‐Julia; Forster, Michael; Scherf, Ullrich
Abstract: Incorporation of the donor–acceptor structure of an alternating conjugated copolymer into a rigid ladder polymer backbone is reported. The resulting ladder polymers show optical features typical of rigid ladder polymers, but present an increased Stokes shift if compared to their non‐polar counterparts. This behavior reflects the occurrence of charge transfer processes during excitation and leads to a positive solvatochromism. Abstract : Up on the ladder : The donor–acceptor structure of an alternating conjugated copolymer was incorporated into a rigid ladder polymer backbone. The resulting ladder polymers show optical features typical of rigid ladder polymers, but present an increased Stokes shift corresponding to charge transfer processes during excitation, leading to a positive solvatochromism.